Two-dimensional transthoracic echocardiography at rest for the diagnosis, screening and management of pulmonary hypertension (Swiss Medical Weekly, 2021)
Doppler echocardiography is widely used in everyday clinical practice for the detection of pulmonary hypertension (PH) in symptomatic patients and in populations particularly at risk of pulmonary arterial hypertension (PAH). It allows accurate estimation of systolic pulmonary arterial pressure but may lack precision in particular situations. In addition, echocardiography can help to distinguish between pre- and post-capillary PH and is a very good tool to evaluate right ventricular systolic function, which is of great prognostic interest in PAH. This article reviews the current knowledge about methodologic aspects of assessing pulmonary pressure and PH origin by echo, including a discussion about abnormal thresholds. It also details advanced techniques like right ventricular strain imaging and new concepts like right ventricle – pulmonary artery coupling evaluation that have become “matured” enough to be definitely brought to routine evaluation.